(untitled) (Geo-Eco-Marina, 2022)
The Cobălcescu’s Elements of Geology (1859) was published in ”livre de poche” (Fig. 1), with 116 text pages and 239 text-figures atlas which was not preserved. It was printed with the Romanian transitional alphabet, and it includes four sections (Figs. 2, 3). Cobălcescu interpreted the data following the French author Beudant (1841) in the detailed much comprehensive. The textbook of Cobălcescu includes only 80 pages with 159 paragraphs, out of the four Lessons of Beudant counting 322 pages (without index) and 254 paragraphs. Although drastically reduced, the author succeeded to use in his textbook a large amount of essentialized geological information. Without being included in the text of the manual, all 239 figures were certainly included in the atlas (some illustrations are reproduced in Fig. 4). Back from France in 1862, Cobălcescu wanted to take the book out of public circulation and began to destroy the textbook where ever he could find it, buying it from bookstores and destroying it as a sin of youth.